2007
DOI: 10.4049/jimmunol.178.4.2589
|View full text |Cite
|
Sign up to set email alerts
|

IL-23 Is Critical in the Induction but Not in the Effector Phase of Experimental Autoimmune Encephalomyelitis

Abstract: Experimental autoimmune encephalomyelitis (EAE), a T cell-mediated inflammatory disease of the CNS, is a rodent model of human multiple sclerosis. IL-23 is one of the critical cytokines in EAE development and is currently believed to be involved in the maintenance of encephalitogenic responses during the tissue damage effector phase of the disease. In this study, we show that encephalitogenic T cells from myelin oligodendrocyte glycopeptide (MOG)-immunized wild-type (WT) mice caused indistinguishable disease w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
118
4
3

Year Published

2008
2008
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 153 publications
(132 citation statements)
references
References 37 publications
6
118
4
3
Order By: Relevance
“…Treatment with anti-IL-23 reduced IL-17 production and attenuated EAU when administered immediately before and after induction of disease, but not at the effector stage of the disease, suggesting that IL-23 promotes the induction of murine Th17 cells in vivo [61]. This conclusion is consistent with a study in the EAE model involving adoptive transfer of T cells into IL-23p19 À/À mice, which concluded that IL-23 played a critical role in the development, but not effector function, of encephalitogenic T cells [62]. These studies, together with findings from my own group, showing that IL-23 can function with IL-1 to promote 'innate' IL-17 production from unconventional T cells in the absence of TCR engagement [25] (and Sutton and Mills, unpublished observations), suggest that the function of IL-23 is not to be confined to expansion of memory T cells.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…Treatment with anti-IL-23 reduced IL-17 production and attenuated EAU when administered immediately before and after induction of disease, but not at the effector stage of the disease, suggesting that IL-23 promotes the induction of murine Th17 cells in vivo [61]. This conclusion is consistent with a study in the EAE model involving adoptive transfer of T cells into IL-23p19 À/À mice, which concluded that IL-23 played a critical role in the development, but not effector function, of encephalitogenic T cells [62]. These studies, together with findings from my own group, showing that IL-23 can function with IL-1 to promote 'innate' IL-17 production from unconventional T cells in the absence of TCR engagement [25] (and Sutton and Mills, unpublished observations), suggest that the function of IL-23 is not to be confined to expansion of memory T cells.…”
supporting
confidence: 87%
“…While the differences observed using different experimental approaches and between human and mouse have not been fully resolved, the picture that is emerging is that multiple cytokines, including IL-1, IL-6, IL-21, TNF-a, IL-23 and TGF-b, stimulated by inflammatory stimuli, including TLR and NLR agonists and during sterile inflammation, can promote the differentiation or expansion of IL-17-secreting T cells. Studies with knockout mice have identified essential roles for IL-1 [25], IL-6 [59], IL-23 [62] and TGF-b [42] in the development of pathogenic T cells that mediated autoimmunity. These cytokines are obvious targets for the development of immunotherapeutics for autoimmune diseases.…”
Section: Conclusion and Prospects For Therapies That Target Th17 Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…5A). These results suggested that exogenous IL-23 was able to stimulate plt/plt mouse DLN cells along with the MOG peptide to induce pathogenic Th17 cells, consistently, with the critical role of IL-23 in the induction phase of EAE (17). Taken all together, these findings suggest that the defect in plt/plt mice is likely a defect in Th17 cell generation due to deficient IL-23 production.…”
Section: Il-23-dependent Induction Of Pathogenic Th17 Cellssupporting
confidence: 53%
“…4, A and D), indicating that the generation of IL-23 in response to CCR7 ligands is required for Th17 cell generation. Supporting this interpretation, recent reports have demonstrated that IL-23 is critically important in inducing Th17 cells (17,39,40). Taken together, it is possible that CCR7 ligands might also increase IL-21 production and IL-23 receptor expression for the optimal induction of Th17 cells.…”
Section: Figurementioning
confidence: 75%